Respon Retoris Perusahaan Terindeks SRI-Kehati terhadap Isu Sosial dan Lingkungan yang Diekspos Media - Rhizma, Putu Ayu Dea; Ardiana, Putu Agus (E-Jurnal Akuntansi; Vol 34 No 8 (2024), 2024)
This study seeks to examine the rhetorical responses of companies indexed by SRI-Kehati to social and environmental issues as presented in their sustainability reports. Additionally, it aims to compare these responses with those from non-indexed companies and to investigate the correlation between negative media exposure and companies' rhetorical strategies. The study encompasses 60 observations and utilizes both qualitative and quantitative analytical approaches. The findings reveal that companies employ a range of rhetorical strategies to address media exposure concerning social and environmental issues. Moreover, the analysis demonstrates a significant difference in rhetorical responses between companies indexed by SRI-Kehati and those that are not. There is also a notable negative correlation between the extent of negative media exposure and the nature of the companies' rhetorical responses, suggesting that increased negative media attention influences the strategies companies adopt in their sustainability reporting. Keywords: Rhetorical Response; Media Exposure; SRI-Kehati Index.